(untitled) (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: The aim of the study was to develop oil-in-water microemulsion (ME) system for Melaleuca alternifolia for targeting skin disorders. Materials and Methods: The formulation of ME system was done through the water titration method, which involved various oils, water, surfactants, and cosurfactants. The existence zones of ME were determined by constructing ternary phase diagrams, where surfactants and cosurfactants (Smix) were taken in different ratios along with different combinations of oil and Smix. Quantitative estimation of tea tree oil (TTO) was performed using gas chromatography-mass spectrometry followed by total terpenoid estimation, and thereafter, solubility studies of TTO were performed using various excipients. TTO-ME was fabricated and characterized using modern characterization techniques (DLS, transmission electron microscopy, and Fourier transform infrared) along with statistical validation and in vitro drug release assessment. Results and Discussion: The optimized TTO loaded MEs (TTO ME) showed the particle size range between 32 and 160 nm with poly dispersibility index of 0.297 and zeta potential of âˆ’3.19 mv with almost spherical morphology. The optimized formulation showed the sustained release of the therapeutic compound and was found to be stable at room temperature for 1 year, suggesting being a promising formulation against dermal infections. Conclusion: TTO was successfully loaded in thermodynamically stable ME system which enhanced its permeation through the transdermal route. Therefore, a novel drug delivery system was introduced, which can be studied on various in vitro and in vivo models further to establish its better therapeutic efficacy for various skin disorders.